HUBUNGAN INDEKS MASSA TUBUH, DURASI OPERASI DAN DOSIS ANESTESI INHALASI DENGAN SUHU TUBUH PADA PASIEN POST OPERASI DENGAN GENERAL ANESTESIA DI RECOVERY ROOM RSUD BANGIL - Heru Nurmansah; Dyah Widodo; Susi Milwati (Poltekkes Kemenkes Malang, 2021)
Postoperative patients with general anesthesia inclined to experience a decrease in body temperature, this study purpose to determine the relationship of body mass index, duration of surgery, and doses of inhalation anesthesia with body temperature in postoperative patients with general anesthesia in the Recovery Room of Bangil Regional Hospital. Correlation research design, a sample of 51 respondents using purposive sampling. The research instruments were observation sheets of body mass index, duration of surgery, dose of inhalation anesthesia and postoperative body temperature. Data were processed using SPSS 25. Pearson Test data analysis, body mass index (p is 0,000), duration of surgery (p is 0,000), and dose of inhalation anesthesia (p is 0.003). Body mass index correlation strength is strong (0.675), the duration of surgery correlation strength is sufficient (minus 0.407), and the dose of inhalation anesthesia correlation strength is sufficient (minus 0.560). It was concluded that body mass index, duration of surgery and dose of inhalation anesthesia were related to postoperative body temperature with general anesthesia in the recovery room at Bangil District Hospital, meaning the greater the body mass index make the higher the body temperature, the longer the operation and the higher the dose of inhalation anesthetics make the lower the body temperature. The closest correlation is body mass index. It is expected that in future studies can develop research by comparing differences in preoperative, intraoperative and postoperative temperatures. Keywords: Body Mass Index, Duration of Operation, Inhalation Anesthetic Dose, Body Temperature, Post Surgery, General Anesthesia